Odd harmonious labeling of step ladder graphs - Jeyanthi P.; Philo S. (Utilitas Mathematica, 2020)
A graph G(p,q) is said to be odd harmonious if there exists an injection f: V(G) → 0, 1, 2, • • •, 2q — 1 such that the induced function f*: E(G) → 1, 3, • • •, 2q -1 defined by f*(uv) = f(u) + f(v) is a bijection. In this paper we prove that path union of t copies of S(Tn) , double sided step ladder 2S (T2×n), path union of t copies of 2S (T2×n), S(t.Cbn), S (tC4), C4t, C6t* and C8t are odd harmonious graphs. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.